New tools for dead roots: Radioisotope labelling and compound‐specific analysis reveal how subsoil hotspots work. Issue 6 (4th September 2022) - Banfield, Callum C.
Abstract: Subsoils are increasingly studied as they, first, store a great deal of terrestrial carbon (C) and possibly even more, and second, offer resources like water and nutrients to plants, potentially mitigating negative consequences of global change. As subsoil access is often hampered by compacted soil layers, the key to accessing subsoil resources and storing more C below ground might be in biopores. Appropriately nicknamed 'highways of root growth', biopores are macropores left behind by dying roots and earthworm activities, often enriched with organic matter (OM) and nutrients. They are thought to be the most abundant microbial hotspots in the subsoil, thus possibly accounting for a large part of C turnover, as well as offering pore wall nutrients to subsequent crops. Understanding the multifunctionality and complexities of biopores remains challenging. This contribution aims to showcase analytical ways to deepen our understanding of origin and functioning of biopores and hotspots. Regarding their biogeochemistry, biopore OM quality and its turnover can be better unravelled through compound‐specific analysis to deduct biopore‐specific OM turnover. Biopores can be reliably differentiated by their OM quality. A more profound understanding of subsoil C turnover in very contrasting hotspots is crucially important for managing subsoil functions. Biopores are often assumed to be beneficial in crop sequences. Roots making use of specific biopores can be, for the first time, quantified after radiotracer application, two‐step phosphor imaging, and image processing. Combining radioactive with stable isotopes as well as plant and microbial biomarkers allows to investigate the relevance of individual pore wall nutrients in plant growth in consideration of physical biopore properties. Biopore‐friendly management practices (e.g., reduced tillage, perennial cover cropping) could be part of smart subsoil management. Faster access to subsoil water and concentrated biopore nutrients may safeguard agricultural production—especially in times of rising fertiliser costs (both monetary and environmental) and more frequent droughts.